Penyusunan Peta Jalur Pendakian Dalam Kegiatan Pengabdian Masyarakat di Gunung Muria - Aziz Akbar Mukasyaf (Universitas Muhammadiyah Surakarta, 2025)
This community service activity was carried out with involving partners from the Mount Muria Trekking Community in Rahtawu Village, Gebog District, Kudus Regency, Central Java. The activity was driven by the absence of an official trekking route map to the Natas Angin Peak and Puncak 29 of Mount Muria, as well as unclear locations of trekking posts, Shelters, water sources, and hazard zones. In fact, this route has significant potential to be developed as an official trekking path that could support the development of Rahtawu Village as a nature-based tourism village. In this activity, the team conducted a field survey using GPS tracking methods to collect position and elevation data at key points. This community service activity was carried out with involving partners from the Mount Muria Trekking Community in Rahtawu Village, Gebog District, Kudus Regency, Central Java. The activity was driven by the absence of an official trekking route map to the Natas Angin Peak and Puncak 29 of Mount Muria, as well as unclear locations of trekking posts, Shelters, water sources, and hazard zones. In fact, this route has significant potential to be developed as an official trekking path that could support the development of Rahtawu Village as a nature-based tourism village. In this activity, the team conducted a field survey using GPS tracking methods to collect position and elevation data at key points along the route. The data obtained was then processed using mapping software (ArcGIS) to produce both digital and printed maps of the Mount Muria trekking routes via Rahtawu. This map serves as a visual information source that includes the trekking route, resting posts, camping areas, water sources, and hazardous or steep zones. It is hoped that the results of this activity can be recommended to basecamp managers and the Mount Muria trekking community to support the legality and safety of the route, as well as serve as a reference for trekkers and the general public. With this map, the trekking route can be more systematically developed and contribute to the improvement of the local economy along the route. The data obtained was then processed using mapping software (ArcGIS) to produce both digital and printed maps of the Mount Muria trekking routes via Rahtawu. This map serves as a visual information source that includes the trekking route, resting posts, camping areas, water sources, and hazardous or steep zones. It is hoped that the results of this activity can be recommended to basecamp managers and the Mount Muria trekking community to support the legality and safety of the route, as well as serve as a reference for trekkers and the general public. With this map, the trekking route can be more systematically developed and contribute to the improvement of the local economy.